Group Investigation and Explicit learning Models in Learning Physics at Senior High Schools - I Wayan Santyasa; I Nyoman Kanca; I Wayan Sukra Warpala; I Komang Sudarma (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
Physics teaching in high school is still dominated by explicit learning models, relatively rarely empowering the potential of group inquiry based on social interaction. This has become one of the reasons for the lack of optimal student learning products. This study aimed to analyze the difference of effect between the group investigation (GI) model and the explicit learning (EL) model in achieving critical thinking skill, social attitude, spiritual attitudes, and student character in learning physics. To achieve this goal, a quasi-experimental study was conducted using a nonequivalence posttest only control group design. The study population was 16 classes (566 people) XI MIPA class students who came from two SMAs, namely 8 classes (280 students) SMA 1 Tabanan and 8 classes (286 students) SMA 1 Kediri Tabanan. The sample in each high school consisted of 2 classes selected by a random assignment technique. The whole sample was 4 classes (140 students, or 24.73% of the total population), 2 classes learned with GI model and 2 classes with the EL model, each learned sound wave and lightwave. Data on students' critical thinking skill was collected by 12 items test. Data on students’ social attitude, spiritual attitude, and character were collected with a social attitude questionnaire which consists of 30 items, a spiritual attitude questionnaire which consists of 30 items, and a character questionnaire which consists of 18 items. The research data were analyzed by one way MANOVA. The results showed that the GI model had a higher effect than the EL model in achieving critical thinking skill, social attitude, spiritual attitude, and the character of the students in learning sound wave and lightwave in high school physics.